Waiting to score. Conversion probability and the video assistant referee (VAR) in football penalty kicks - Veldkamp, J.; Koning, R. H. (Journal of Sports Sciences, 2023)
The VAR has introduced a new element to football. Before, a decision to award a penalty kick could not be reversed. The player taking the penalty could take it relatively quickly after the referee called the foul. After the introduction of the VAR, every penalty kick decision is replayed by the VAR and also quite often reviewed on-field. As a consequence, time between the initial decision by the referee and the actual penalty kick has increased substantially. We examined the influence of the time-interval duration between the foul and the actual penalty kick on the conversion probability using a logit model. Also, we assessed the consequences of a VAR intervention, if any. We used data on all 2888 penalties awarded in top leagues in England, Spain, Germany, Italy, the Netherlands, and the UEFA Champions League, over the course of five seasons (2015/2016-2019/2020). We found that the duration between the foul and the moment the penalty is taken does not impact the conversion probability. However, whether or not the VAR intervenes with the referee`s decision has a negative effect on the conversion probability of penalty kicks. Football teams and coaches should incorporate this element of uncertainty in training.